Integrating Human Resource Information System into Educational Institutions: A Framework for Digital Culture Adaptation - Bahri, Danang Zainal Ali; Basuki, Basuki; Zamrudi, Zakky (JURNAL AL-TANZIM, 2024)
The application of technology in human resource management in the education sector aims to improve efficiency, transparency, and accountability in managing school personnel data. This study aims to analyze the application of technology in human resource management in the education sector, focusing on using the Personnel Management Information System and the Human Resource Information System to improve efficiency, transparency, and accountability in managing personnel data in schools. This study uses a qualitative design with a case study approach. Data were collected through interviews, observations, and document analysis, then analyzed using qualitative data analysis techniques through three stages: data reduction, data presentation, and data verification. The study results indicate that applying technology through the Personnel Management Information System and the Human Resource Information System can improve efficiency, transparency, and professionalism in human resource management in education. However, the main challenges are the uneven distribution of infrastructure and limited digital skills in remote schools. This study implies the importance of continuous digital skills training for educators and improving technological infrastructure in schools, especially in remote areas, to support the practical application of technology in human resource management in education.